Complexité et enjeux des mailles territoriales. Variations à partir du cas tunisien - Myriam Baron; Sophie de Ruffray; Walid Achouri; Khaoula Saadaoui; Ali Bennasr; Claude Grasland (L’Année du Maghreb)
The period that begins with the reflections and debates around the new constitution in Tunisia is also the one of territorial reform. Questions about it and, more generally, about the recasting of local authorities and equalization rules has emerged as a major political and social issue. This article shows that what is played out in this country cannot free itself on the one hand from the territorial grids that have existed for several decades, on the other hand from the urban fact that takes more and more importance in the structuring of activities and wealth. This article finally stresses the need to take account of the representations and perceptions of the populations to carry out such a reform.